2020
DOI: 10.1002/jcla.23164
|View full text |Cite
|
Sign up to set email alerts
|

Long intergenic non‐coding RNA 511 correlates with improved prognosis, and hinders osteosarcoma progression both in vitro and in vivo

Abstract: Background:This study aimed to investigate the correlation of long intergenic noncoding RNA 511 (LINC00511) with clinicopathological characteristics and overall survival (OS) in osteosarcoma patients and to explore its function in osteosarcoma in vitro and in vivo. Methods:Tumor tissues and adjacent tissues from 45 osteosarcoma patients were acquired, and LINC00511 expression was detected. In vitro, LINC00511 expression was detected in osteosarcoma cell lines and osteoblast cell line. LINC00511 overexpression-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Next, these 73 studies were carefully screened by the titles, abstracts, and full texts. Finally, a total of 13 eligible studies comprising 1053 cancer patients were included according to the inclusion and exclusion criteria in this meta-analysis [ 9 , 10 , 16 , 17 , 21 , 22 , 25 , 28 , 33 35 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, these 73 studies were carefully screened by the titles, abstracts, and full texts. Finally, a total of 13 eligible studies comprising 1053 cancer patients were included according to the inclusion and exclusion criteria in this meta-analysis [ 9 , 10 , 16 , 17 , 21 , 22 , 25 , 28 , 33 35 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 26 , 27 ] Nevertheless, some studies also reported that LINC00511 could be a tumor suppressor, with high LINC00511 expression being associated with favorable prognosis of some cancer patients. [ 28 ]…”
Section: Introductionmentioning
confidence: 99%
“…Long intergenic noncoding RNA 00511 (LINC00511) is a newly identified lncRNA and has been reported to be dysregulated in various malignant tumors, including glioma [7], ovarian cancer [8], breast cancer [9,10], cervical cancer [11,12], osteosarcoma [13], lung cancer [14], hepatocellular carcinoma [15][16][17], renal cell cancer [18], pancreatic cancer [19], gastric cancer [20][21][22], tongue squamous cell carcinoma [23] and papillary thyroid carcinoma [24]. To date, most literature suggested that LINC00511 was aberrantly upregulated in malignant tumors and its high expression correlated with poor survival of patients with glioma [7], ovarian cancer [8], breast cancer [9,10], cervical cancer [11,12], osteosarcoma [13], lung cancer [14], gastric cancer [22], hepatocellular carcinoma [15], renal cell cancer [18] or pancreatic cancer [19]. Furthermore, those studies revealed that LINC00511 could accelerate tumor progression by inhibiting malignant cell apoptosis and promoting tumor cell proliferation, migration, invasion, metastasis, chemotherapy resistance, and so on [10,11,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, the association between LINC00511 expression and prognosis of patients with malignant tumor is still controversial. For example, Qiao et al [13] reported that LINC00511 was downregulated in osteosarcoma, which was related to improved survival. Additionally, they further demonstrated that upregulation of LINC00511 could impede the progression of osteosarcoma through inducing apoptosis and suppressing the migration and invasion of osteosarcoma cells [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation